Role of toll-like receptor 4 and sex in 6-hydroxydopamine–induced behavioral impairments and neurodegeneration in mice. (December 2021) - Somensi, Nauana; Lopes, Samantha Cristiane; Gasparotto, Juciano; Mayer Gonçalves, Rosângela; Tiefensee-Ribeiro, Camila; Oppermann Peixoto, Daniel; Ozorio Brum, Pedro; Pinho, Cibele Martins; Agnes, Jonathan Paulo; Santos, Lucas; de Oliveira, Jade; Spiller, Fernando; et al.
Abstract: Parkinson's disease (PD) is a neurodegenerative disease characterized by progressive loss of the nigrostriatal dopaminergic neurons that are associated with motor alterations and non-motor manifestations (such as depression). Neuroinflammation is a process with a critical role in the pathogenesis of PD. In this regard, toll-like receptor 4 (TLR4) is a central mediator of immune response in PD. Moreover, there are gender-related differences in the incidence, prevalence, and clinical features of PD. Therefore, we aimed to elucidate the role of TLR4 in the sex-dependent response to dopaminergic denervation induced by 6-hydroxydopamine (6-OHDA) in mice. Female and male adult wildtype (WT) and TLR4 knockout ( TLR4 −/− ) mice were administered with unilateral injection of 6-OHDA in the dorsal striatum, and non-motor and motor impairments were evaluated for 30 days, followed by biochemistry analysis in the substantia nigra pars compacta (SNc), dorsal striatum, and dorsoventral cortex. Early non-motor impairments (i.e., depressive-like behavior and spatial learning deficits) induced by 6-OHDA were observed in the male WT mice but not in male TLR4 −/− or female mice. Motor alterations were observed after administration of 6-OHDA in both strains, and the lack of TLR4 was also related to motor commitment. Moreover, ablation of TLR4 prevented 6-OHDA–induced dopaminergic denervation and microgliosis in the SNc, selectively in female mice. These results reinforced the existence of sex-biased alterations in PD and indicated TLR4 as a promising therapeutic target for the motor and non-motor symptoms of PD, which will help counteract the neuroinflammatory and neurodegenerative processes. Graphical abstract: Image 1 Highlights: "TLR4 regulates early depressive-like behaviors induced by 6-OHDA in male mice". "Females have late behavior effects and more robust immune response to 6-OHDA". "6-OHDA-induced DA denervation and glial reactivity is prevented by TLR4−/− in females". "TLR4 modulates neuroinflammation in gender-specific manner.".